A ficção nos escritos de alma de Nelson Rodrigues e Chico Bicudo: a crônica esportiva em dois tempos - Gabriel Canuto Nogueira da Gama (2018)
In the light of theoretical concepts that surround the border genre of the chronicle, the complex phenomenon of fiction and the literary and journalistic discourses, this work has the main proposal to identify and analyze the processes of fictionalization in sports chronicles, from the comparison of the production of different epoques. Nelson Rodrigues and Chico Bicudo have been separated by more than six decades, however, they have both carried similarities as vivid witnesses of those two biggest humiliations in our football history: the indelible defeats in 1950 and 2014 World Cups. Based on those historical events which crystallized in the collective memory of the Brazilian people, unleashed dramatic narratives and since then carry a mythical aura, the dissertation peers the nuances of three fictional elements orality, hyperbole and fable used by the two chroniclers in the tessitura of their texts. It is important to emphasize that the research does not aim a qualitative distinction of these productions, nevertheless, a comparative analysis regarding the similarities and specificities of those two writers through the imbricated relation between fact and fiction which permeates the genre. Upon this research, we hope to contribute for the dear football Brazilian studies throughout the mission of demystifying it from the image of opium of the masses, reinforcing its function of been an authentic identity and cultural element of the Brazilian people.